Preparation, characterization, and scaffolding capacity of chitosan/gellan gum-based hydrogel assemblies - Oliveira, Ariel Colaço de (2018)
In this study, we have demonstrated the production and characterization of hydrogels based on chitosan and gellan gum (CS/GG) assemblies. Hydrogels were created without any covalent and metallic crosslinking agents, conventionally used to yield polysaccharide-based hydrogels. Polyelectrolyte complexes (PECs) were characterized by infrared spectroscopy (FTIR), thermal analysis (TGA and DSC), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and wide-angle X-ray scattering (WAXS). Hydrogels containing chitosan (CS) contents ranging from 40 to 80 wt.% were yielded by performing CS/GG blends at 60°C. CS/GG wt.%/wt.% ratio was modulated in the blend to promote hydrogels with interconnected pore networks, structural homogeneity, durability, and hydrophilicity. These properties are required in the development of scaffold-based platforms. The polymer chains in the hydrogel matrices have self-assembled during the neutralization step. The reorganization was confirmed through TGA, DSC, and SEM techniques. A hydrogel prepared from the CS/GG 60/40 ratio (sample CS/GG(60-40)) showed swelling degree (SD%) of 6460% after 4 days in PBS buffer. This PEC had no potential to act as scaffold matrix; however, a cytocompatible CS/GG hydrogel yielded at 80/20 CS/GG ratio (sample CS/GG80-20) supported fixation, growth, and spreading of bone mesenchymal stem cells (BMSCs) after 9 days of cell culture. This hydrogel exhibited desirable properties to be applied in tissue engineering arena.